IMPLEMENTATION OF LAW NUMBER 8 OF 2010 CONCERNING THE PREVENTION AND ERADICATION OF THE CRIME OF MONEY LAUNDERING (TPPU) ON ENFORCEMENT OF MONEY LAUNDERING CRIMINAL LAWS REGARDING FORESTRY CRIME (ILLEGAL LOGGING) - Rolando Marpaung; Dikki Saputra Saragih; Parlindungan Purba; Judof Wenjel Putra (Journal of International Islamic Law, Human Right and Public Policy, 2023)
This journal specifically explores the implementation of Law Number 8 of 2010, which addresses the issue of money laundering related to forestry crimes. The main objective of the journal is to outline and concretely evaluate the measures implemented in accordance with the legal framework, with an emphasis on their impact on efforts to overcome illegal practices that threaten forest sustainability. This journal provides concrete recommendations for further improvements in the implementation of Law Number 8 of 2010, including proposals to strengthen inter-institutional cooperation, increase resources, and increase public awareness. Through this approach, this journal seeks to not only present a retrospective analysis, but also provide a basis for improving future policies and actions that are more effective in protecting forest sustainability from the threat of forestry-related money laundering.